Martuwarra Fitzroy River Council: an Indigenous cultural approach to collaborative water governance. Issue 3 (3rd July 2019) - Poelina, Anne; Taylor, Kathrine S.; Perdrisat, Ian
ABSTRACT: In 2016, Traditional Owners came together to discuss their collective vision for the Martuwarra, expressed in the Fitzroy River Declaration. Traditional Owners established the Martuwarra Fitzroy River Council (MFRC) as a collective governance model to maintain the spiritual, cultural and environmental health of the catchment. Traditional Owners advocate a collaborative approach for an inclusive water governance model and catchment management plan. The MFRC advocates the need to establish a Fitzroy River Catchment Authority as a statutory body to monitor and regulate potential cumulative impacts from development. The Authority needs to be inclusive of all stakeholders and ensure that there is informed consent in decisions regarding development. This article articulates a local critique of water resource development and presents an alternative model of governance developed by Indigenous leaders of the West Kimberley.